CSR and GCG on Company Performance: Insights from the Triple Bottom Line - Ida Bagus Gde Indra Wedhana Purba; I Gusti Bagus Wiksuana; Luh Gede Sri Artini; Ica Rika Candraningrat (Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the interconnections between Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and company performance using the Triple Bottom Line (TBL) framework as a conceptual foundation. The increasing demand for corporate accountability and sustainable business practices has encouraged organizations to integrate CSR initiatives with strong governance mechanisms to improve overall performance. Previous studies have shown that CSR and GCG play essential roles in enhancing corporate reputation, stakeholder trust, and long-term business sustainability, yet the integration of these concepts within the TBL perspective remains underexplored. This study employs a systematic literature review approach by analyzing relevant academic publications related to CSR, GCG, TBL, and company performance. Bibliometric analysis using VOSviewer software is applied to identify research trends, thematic relationships, and the evolution of scholarly discussions in this field. The analysis reveals that companies implementing CSR activities supported by strong GCG structures tend to achieve better financial performance, improved social responsibility outcomes, and stronger environmental sustainability practices. The findings indicate that the integration of CSR and GCG within the TBL framework positively influences company performance by strengthening organizational legitimacy, improving stakeholder relationships, and supporting sustainable long-term profitability. In conclusion, the study confirms that CSR initiatives are more effective when supported by robust governance practices and aligned with TBL principles. Therefore, companies are encouraged to strategically integrate CSR and GCG into their business models to achieve sustainable performance and competitive advantage.